AḤMAD B. AL-ṬAYYIB AL-SARAḪSĪ, RÉVISEUR DE L'INTRODUCTION ARITHMÉTIQUE DE NICOMAQUE DE GÉRASE ET RÉDACTEUR DES RASĀ᾿IL IḪWĀN AL-ṢAFĀ᾿. Issue 2 (September 2019) - de Vaulx D'Arcy, Guillaume
Abstract: Before Ṯābit b. Qurra's translation, there was a first Arabic version of Nicomachus' Introduction to arithmetic . Full of mistakes, it was revised by an anonymous student of al-Kindī. Thanks to the part that Freudenthal and Levy have edited and translated, we are now able to identify this reviser as Aḥmad b. al-Ṭayyib al-Saraḫsī, who we also identified as the author of the Rasā᾿il Iḫwān al-Ṣafā᾿ . The comparison of the gloss written by this reviser with a new fragment of Saraḫsī on one part, and with the " Epistles of the Brethren in Purity " on the other, corroborate Saraḫsī's authorship of the epistles. Furthermore, studying the misunderstandings on Nicomachus' text in this kindianised version gives a new light on al-Kindī's attempt to unify philosophy and on the specific ontology of the Brethren in Purity. Résumé: Avant celle de Ṯābit b. Qurra, l' Introduction arithmétique de Nicomaque de Gérase fit l'objet d'une première traduction fautive révisée par un élève d'al-Kindī. Grâce à la partie éditée et traduite par Freudenthal et Lévy, nous pouvons désormais identifier ce réviseur comme étant Aḥmad b. al-Ṭayyib al-Saraḫsī, que nous avons par ailleurs reconnu comme auteur des Rasā᾿il Iḫwān al-Ṣafā᾿ . La comparaison des gloses de ce réviseur d'une part avec un fragment inédit d'al-Saraḫsī et d'autre part avec les « Épîtres des Frères en Pureté » corrobore l'attribution des épîtres à al-Saraḫsī. En outre, l'étude des contresens de cette version kindisée du texte de Nicomaque nous renseigne mieux tant sur la tentative kindienne d'unifier la philosophie que sur la spécificité de l'ontologie des Frères en Pureté.